2022
DOI: 10.2217/pgs-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pharmacogenetics-Based Fluvoxamine Use as an Add-On to Clozapine Treatment in Psychiatry

Abstract: Pharmacological treatments used for psychiatric disorders, such as clozapine, demonstrate large interindividual variability in terms of possible adverse effects and therapeutic benefit. This variability can be explained by multiple factors, including pharmacogenetic factors. Clozapine efficacy can be impacted by CYP polymorphisms. A growing body of literature on pharmacogenetics suggests the clinical benefit of concomitant use of clozapine and fluvoxamine to improve global pharmacotherapeutic management. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Treatment strategies for psychiatric disorders often involve psychotherapy and pharmacotherapy� There are more than 200 pharmacotherapies available for treating psychiatric disorders, many of which have unique cellular targets and mechanisms of action� 6,7 Although many people with psychiatric disorders can manage their symptoms with pharmacological interventions, it can be challenging to find the most appropriate treatment for each patient due to the wide array of available drugs and the large interindividual variability in response� 8,9 For example, it has been reported that a clinically significant response is not reached with initial antidepressant medication in as many as 50% of people with major depressive disorder� 10 Consequently, many people with psychiatric disorders go through a trial-and-error process, during which drugs and doses are sequentially trialled before a suitable regimen of pharmacotherapy is found that can help adequately manage symptoms� 11 The trial-and-error phase is often characterized by poor symptom control and adverse side effects, which can cause dissatisfaction and treatment discontinuation� [11][12][13] Precision medicine, also known as personalized medicine, is an approach that tailors treatment decisions based on individual differences in genetics, lifestyle, and other factors� 14 Pharmacogenomics, which is the study of how genes affect a person's response to particular drugs, is 1 of the core elements of precision medicine. Genetic variations can influence the absorption, distribution, metabolism, and excretion of medications� 15 These variations contribute to the interindividual variability in response to psychotropic medications and are therefore particularly relevant in the field of psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment strategies for psychiatric disorders often involve psychotherapy and pharmacotherapy� There are more than 200 pharmacotherapies available for treating psychiatric disorders, many of which have unique cellular targets and mechanisms of action� 6,7 Although many people with psychiatric disorders can manage their symptoms with pharmacological interventions, it can be challenging to find the most appropriate treatment for each patient due to the wide array of available drugs and the large interindividual variability in response� 8,9 For example, it has been reported that a clinically significant response is not reached with initial antidepressant medication in as many as 50% of people with major depressive disorder� 10 Consequently, many people with psychiatric disorders go through a trial-and-error process, during which drugs and doses are sequentially trialled before a suitable regimen of pharmacotherapy is found that can help adequately manage symptoms� 11 The trial-and-error phase is often characterized by poor symptom control and adverse side effects, which can cause dissatisfaction and treatment discontinuation� [11][12][13] Precision medicine, also known as personalized medicine, is an approach that tailors treatment decisions based on individual differences in genetics, lifestyle, and other factors� 14 Pharmacogenomics, which is the study of how genes affect a person's response to particular drugs, is 1 of the core elements of precision medicine. Genetic variations can influence the absorption, distribution, metabolism, and excretion of medications� 15 These variations contribute to the interindividual variability in response to psychotropic medications and are therefore particularly relevant in the field of psychiatry.…”
Section: Introductionmentioning
confidence: 99%